IVAN FRANKO WHOM WE DO NOT KNOW… (OF KAMENIAR’S RELIGIOUS VIEWS) - Smytsniuk, O. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reads about I.Franko’s attitude to Christian religion; religious issues reflected in I.Franko’s poetry, prose and scientific works; relationships between Metropolitan A.Sheptytsky and I.Franko.